A Distinct Difference Between Air and Mucosal Temperatures in Human Respiratory Tract - Khosravi, Mehdi; Lin, Ruei-Lung; Maskey, Ashish P.; Pandey, Subodh; Lin, An-Hsuan; Lee, Lu-Yuan (Frontiers in Medicine, 2021)
Extensive evidence indicates that several types of temperature-sensitive ion channels are abundantly expressed in the sensory nerves innervating airway mucosa. Indeed, airway temperature is known to play an important role in regulating respiratory functions. However, the actual airway mucosal temperature and its dynamic changes during the respiratory cycle have not been directly measured. In previous studies, airway tissue temperature was often estimated by indirect measurement of the peak exhaled breath temperature (PEBT). In view of the poor thermal conductivity of air, we believe that the airway tissue temperature cannot be accurately determined by the exhaled air temperature, and this study aimed to test this hypothesis. We applied a miniature rapid-response temperature probe to measure directly the mucosal temperatures of trachea, major, lobar and segmental bronchi in eight human subjects during a bronchoscopy procedure. Unlike the air temperature in the airway lumen, the mucosal temperature in these airway segments remained relatively stable and did not exhibit the phasic changes synchronous with respiratory cycles. The airway mucosal temperature increased progressively from the extra-thoracic trachea (35.7±0.2°C) toward the segmental bronchus (36.9±0.2°C). Most importantly, the temperatures measured directly at the mucosa of all these airway segments were substantially higher than the PEBT (31.7±0.8°C). The recent findings of a close association between an increased PEBT and airway tissue inflammation have revealed the implication and potential of incorporating the PEBT measurement in the future clinical diagnosis of airway inflammation. Therefore, it is imperative to recognize this distinct difference in temperature between airway mucosa and exhaled air.